How the Arcetri Astronomical Observatory became Astrophysical - Bianchi, Simone (Il Colle di Galileo, 2021)
One hundred years ago, on 12 May 1921, a Royal Decree changed the name of the Arcetri Observatory from “Astronomical” to “Astrophysical”. Here we recount the stages of this transformation, highlighting the role played by Director Antonio Abetti.